Imagem de marca: um estudo de caso VIEMAR - Monteiro, Maria Augusta Priori (Universidade do Vale do Rio dos Sinos, 2012)
The case study aims to analyze the Brand Image of VIEMAR AUTOMOTIVE INDUSTRY. We sought to examine the theories of Integrated Marketing Communications, Brand, Consumer Behavior and Market B2B to substantiate this study. We tried to quantitative and qualitative research to identify the perceptions of VIEMAR among various stakeholders. We used the technique of content analysis to compare the results of research on the strategies used to build brand. The analysis of case leads to the conclusion that the image which customers have VIEMAR brand.
Keywords: Marca; Imagem de Marca; Brand; Brand image